Disentangling direct and indirect effects of water availability, vegetation, and topography on avian diversity - Remeš, Vladimír; Harmáčková, Lenka (Scientific reports, 2018)
Climate is a major driver of species diversity. However, its effect can be either direct due to species physiological tolerances or indirect, whereby wetter climates facilitate more complex vegetation and consequently higher diversity due to greater resource availability. Yet, studies quantifying both direct and indirect effects of climate on multiple dimensions of diversity are rare. We used extensive data on species distributions, morphological and ecological traits, and vegetation across Australia to quantify both direct (water availability) and indirect (habitat diversity and canopy height) effects of climate on the species richness (SR), phylogenetic diversity (PD), and functional diversity (FD) of 536 species of birds. Path analyses revealed that SR increased with wetter climates through both direct and indirect effects, lending support for the influence of both physiological tolerance and vegetation complexity. However, residual PD and residual FD (adjusted for SR by null models) were poorly predicted by environmental conditions. Thus, the FD and PD of Australian birds mostly evolved in concert with SR, with the possible exception of the higher-than-expected accumulation of avian lineages in wetter and more productive areas in northern and eastern Australia (with high residual PD), permitted probably by older biome age.
Keywords: Animals; biodiverzita; Birds; Ecology; ekologie; Australia; rostliny; ptáci; Austrálie; voda; Phylogeny; Water; podnebí; Biodiversity; Plants; ekosystém; Ecosystem; zvířata; Climate; fylogeneze